Dynamics of peripheral blood auto-rosette formation in treated patients with essential arterial hypertension - V. S. Volkov; L. N. Korichkina (Кардиоваскулярная терапия и профилактика, 1970)
Aim. To study intravascular auto-rosette formation (ARF) in peripheral blood of patients with essential arterial hypertension (EAH) during antihypertensive treatment (AHT). Material and methods. In total, 160 EAH patients were examined, including 30 with first-diagnosed EAH, 100 treated occasionally, and 30 receiving regular AHT for several years. Total white blood cell and auto-rosette count, red blood cell mean size, deformation characteristics, osmotic resistance (RBC OR), blood hemoglobin (Hb) level were measured. Results. In EAH patients, increased number of AH medications taken was associated with increase in total number of auto-rosettes and RBC lysis auto-rosettes, together with reduced RBC OR. In Stage III EAH patients, regularly receiving AHT, a clinically insignificant decrease in RBC count was observed. Conclusion. In treated EAH patients, peripheral blood auto-rosette count is higher than in healthy individuals. Increased ARF is typical for regular AHT, being maximal in individuals receiving AHT for several years, and is associated with reduced RBC count.